Peran Guru Agama dalam Pengembangan Kreativitas Siswa di Anuban Muslim Songkhla School - Andini Arafah; Selamat Pohan (Journal on Education, 2023)
Creative teachers are teachers who have creativity or as innovators. So that their creativity does not appear suddenly, but rather a lot of experience gained by the teacher in the learning process by preparing learning methods, preparing the devices used, and the material to be delivered in the learning process. This study aims to reveal the creativity of Islamic Religious Education teachers in the formation of the character of the students of State the anubanmuslimSongkhlaschool .This study used a qualitative approach with case study design. Data was collected by using interview, observation and documentation techniques. The results of the study show that: (1) are able to convey material with creative models and methods and provide examples for students both inside and outside of learning, (2) need a process to instill character and instill students' awareness, (3) there is encouragement and motivation (press) from within is the principal and teachers, while encouragement from outside is parents, traditional leaders and local government. (4)The realization of character habituation that is always applied in the school environment or in the community. (5) The supporting factor for the realization of character habituation in schools comes from school principals, teachers and local governments, while the inhibiting factor is the difficulty of communicating with students and the community due to differences in language.